Phenotypic diversity of Amaranthus quitensis Kunth landraces: A millenary crop of Ecuadorian Andean region - Delgado, Hipatia (2022)
The black amaranth (Amaranthus quitensis Kunth) is traditionally cultivated in the Ecuadorian highlands, where it has great social, cultural and food importance for the native population, and locally it is called ataco or sangorache. Currently, there are no data on the diversity and conservation status in which the ataco landraces are found. We have evaluated the phenotypic diversity of black amaranth landraces collected at two different times (1981-1986 and 2014-2015) in three representative Andean provinces for this crop (Imbabura, Tungurahua and Cañar). Thirty agro-morphological descriptors were used, 11 quantitative and 19 qualitative. Most of the quantitative traits showed high levels of variation, especially grain yield per plant. The qualitative traits showed less diversity, although the characters related to the plant pigmentation and the shape and attitude of the inflorescence were significantly discriminating between accessions from different provinces. Few significant differences were detected between both collects, so the farmers seem to be carrying out adequate on-farm conservation of the ataco germplasm. The agro-morphological information obtained in this study may be useful for enhancing the use of this plant genetic resource in future amaranth breeding programs, as well as for effectively managing the black amaranth collection from Germplasm Bank of the Ecuadorian National Institute for Agricultural Research (INIAP).